Economic Evaluation of Combined Heat and Power Integrated With Food Waste-Based Ethanol Production - Shafinas Muhammad, Noor Intan; Rosentrater, Kurt A. (Frontiers in Energy Research, 2021)
The concern of food waste (FW) impact on the environment, society and economy, has triggered the researcher to find an alternative way to utilize it. FW is rich with glucose and has the potential to be converted into value-added products such as ethanol. Ethanol is organic materials that have a high demand from different industries such as fuel, beverages, pharmaceutical, and other industrial application. FW fermentation in producing ethanol is a promising method and expected to receive a positive impact on the economy. However, the product price is probably challenging to compete with corn ethanol due to low yield and inconsistency of FW composition. Thus, to increase the profitability, conventional plant integrated with combined heat and power (CHP) system could be a great combination and was conducted in this study. Solid waste stream from the process can be converted into energy and could reduce the utility cost. Therefore, the main focus of this study is to evaluate the economic impact of this integrated system by estimate the minimum selling ethanol (MSE) price using techno-economic analysis (TEA). Results from this analysis showed that the MSE value for this integrated system was 1.88 per gallon. This study suggests that the integrated system with CHP was found to be more economical and attractive to be implemented in commercial scale.